2020
DOI: 10.1364/oe.384760
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing stimulated Raman scattering in kW-level continuous-wave MOPA fiber laser based on long-period fiber gratings

Abstract: Two long-period fiber gratings (LPFGs) used to separately suppress the stimulated-Raman-scattering (SRS) in the seed and amplifier of kW-level continuous-wave (CW) MOPA fiber laser are developed in this paper. A process that combines constant-low-temperature and dynamic-high-temperature annealing was employed to reduce the thermal slopes of 10/130 µm (diameter of core/cladding fiber) and 14/250 LPFGs, used in the seed and amplifier respectively, from 0.48 °C/W to 0.04 °C/W and from 0.53 °C/W to 0.038 °C/W. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Another seed characteristic is the Raman noisy in the seed light. It was found that the Raman noisy can obviously enhance SRS in the high-power Yb-doped fiber amplifiers [18], which can be effectively lowered with the Raman filter such as the tilted fiber Bragg gratings (TFBGs) [15], [26] or long period gratings (LFBGs) [27]- [29]. Furthermore, the seed average power also plays an important role in SRS threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Another seed characteristic is the Raman noisy in the seed light. It was found that the Raman noisy can obviously enhance SRS in the high-power Yb-doped fiber amplifiers [18], which can be effectively lowered with the Raman filter such as the tilted fiber Bragg gratings (TFBGs) [15], [26] or long period gratings (LFBGs) [27]- [29]. Furthermore, the seed average power also plays an important role in SRS threshold.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrogen molecules and hydroxyl compounds have great infrared absorption ability, resulting in heating or even burning of the PS-LPFG when kilowatt-level power passes through it. To promote the capacity of our PS-LPFG to carry high-power laser, our proposed dual annealing method is adopted [20,23] . The constant-low-temperature annealing (60 • C for 30 days) is applied to volatilize the hydrogen molecules and the dynamic-high-temperature annealing is utilized to make the hydroxyl compounds be evaporated away from the PS-LPFG.…”
Section: Fabricationmentioning
confidence: 99%
“…The experimental results showed that LPFGs can effectively suppress SRS in a pulsed fiber laser. In 2020, we utilized LPFGs to suppress SRS in the seed and amplifier of a kilowatt-level MOPA system separately [23] . It is well known that the distance between the wavelength of the Raman light and the wavelength of signal laser is over dozens of nanometers, which means SRS is an independent spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LPFGs were applied in temperature or stress detection [ 5 , 6 , 7 , 8 ]. Except for applications in fiber sensors, researchers applied LPFGs as spectral filtering devices in fiber lasers [ 9 , 10 , 11 , 12 ]. For example, LPFGs have been used to suppress the stimulated Raman scattering (SRS) effect in high-power fiber lasers, where core-guided SRS light can be stripped out of the core by inserting LPFGs, and the proportion of signal light in the output terminal can be increased [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for applications in fiber sensors, researchers applied LPFGs as spectral filtering devices in fiber lasers [ 9 , 10 , 11 , 12 ]. For example, LPFGs have been used to suppress the stimulated Raman scattering (SRS) effect in high-power fiber lasers, where core-guided SRS light can be stripped out of the core by inserting LPFGs, and the proportion of signal light in the output terminal can be increased [ 9 , 10 , 11 ]. By inscribing LPFGs in an erbium-doped fluoride glass fiber, Heck et al proposed a new concept to mitigate the parasitic laser effect in mid-infrared fiber amplifiers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%